Ozone Therapy On Rats Submitted To Subtotal Nephrectomy: Role Of Interleukin 6 And Antioxidant System - Calunga Fernandez, Jose Luis; Menéndez Cepero, Silvia Silvia; Zamora Rodríguez, Zullyt (Revista Cubana de Investigaciones Biomédicas, 2019)
Chronic renal failure (CRF) represents a world health problem. Ozone increases the endogenous antioxidant defense system, preserving the cell redox state. The aim of this study is to evaluate the effect of ozone/oxygen mixture in the renal function, morphology, and biochemical parameters, the rol of cytokine number 6 in an experimental model of CRF (subtotal nephrectomy). Ozone/oxygen mixture was applied daily, by rectal insufflation (0.5 mg/kg) for 15 sessions after the nephrectomy. Renal function was evaluated, as well as different biochemical parameters, at the beginning and at the end of the study(10 weeks). Renal plasmatic flow (RPF), glomerular filtration rate (GFR), the urine excretion index, and the sodium and potassium excretions (as a measurement of tubular function) in the ozone group were similar to those in Sham group. Nevertheless, nephrectomized rats without ozone (positive control group) showed the lowest RPF, GFR, and urine excretion figures, as well as tubular function.. Serum creatinine values and protein excretion in 24 hours in the ozone group were decreased compared with nephrectomized rats, but were still higher than normal values. Histological study demonstrated that animals treated with ozone showed less number of lesions in comparison with nephrectomized rats. Proinflammatory cytokine (IL-6) was decrease in renal tissue after ozone by rectal insunnflation. However, ozone/oxygen mixture induced a significant stimulation in the enzymatic activity of CAT, SOD, and glutathione peroxidase, as well as reduced glutathione in relation with Sham and positive control groups. In this animal model of CRF, ozone rectal administrations produced a delay in the advance of the disease, protecting the kidneys against vascular, hemorheological, and oxidative mechanisms. This behavior suggests ozone therapy has a protective effect on renal tissue by down regulation of the oxidative stress and proinflammatory cytokine shown in CRF.